Hyaluronic Acid Conjugates of Vorinostat and Bexarotene for Treatment of Cutaneous Malignancies. Issue 10 (2nd August 2020) - Sallam, Marwa A.; Prakash, Supriya; Krishnan, Vinu; Todorova, Kristina; Mandinova, Anna; Mitragotri, Samir
Abstract: Skin cancer is the most common class of malignancies in humans with increasing incidence worldwide. Although surgery remains the most common treatment approach, relapses after surgery necessitate other treatment options. There is an increasing clinical demand for topical treatments for skin cancer that can improve the drug's cutaneous localization while limiting systemic absorption. In this study, hyaluronic acid (HA) conjugates are successfully synthesized by attaching a third‐generation retinoid (bexarotene) and a histone deacetylase inhibitor (vorinostat) to HA via ester bonds. The conjugates are characterized to ensure identity and quantify total drug loading. HA‐BEX and HA‐VOR exhibit a synergistic anticancer effect against human squamous cell carcinoma (A431) and human cutaneous T cell lymphoma cell lines (HUT 78) at specific ratios with minimal adverse effect on primary human keratinocytes and fibroblasts. Confocal microscopy demonstrates localization of the conjugates inside the cancer cells. Ex vivo skin permeation studies on human skin explants confirm their ability to penetrate the stratum corneum and reach the deep dermis. Biodistribution studies in the skin reveal the presence of both drugs in the epidermis and dermis in amounts sufficient to exert inhibitory effect on cancer cells. HA‐bexarotene‐vorinostat conjugates offer an excellent therapeutic option to treat skin cancers. Abstract : Hyaluronic acid conjugates of bexarotene and vorinostat exhibiting a synergistic activity against human squamous cell carcinoma and cutaneous T cell lymphoma with minimal adverse effect on normal skin cells are developed. The conjugates penetrate the stratum corneum and reach the deep dermis in amounts sufficient to exert therapeutic effect. HA‐bexarotene‐vorinostat conjugates offer an excellent therapeutic option to treat skin cancers.